Incorporation field crop residues in rabbit rations - Omer, H.A. A. (2021)
Except for organic matter (OM) digestibility, treatments had no effect on all other nutrient digestibilites that includes dry matter (DM), crude protein (CP), crude fiber (CF), ether extract (EE), and nitrogen free extract (NFE) and nutritive values {total digestible nutrient (TDN) and digestible crude protein (DCP)}. Instead, 50% of BH by the other alternative source of agriculture by-products had no effect on all carcass parameters measured. However, dressing percentages was improved. Treatments had no effect on albumin, total lipids, triglycerides, total cholesterol, low-density lipoprotein (LDL), glutamic oxaloacetic transaminase (GOT), creatinine, and alkaline phosphatase.